PENERAPAN ALGORITMA NAIVE BAYES TERHADAP TARGET PENJUALAN HANDPHONE MENGGUNAKAN APLIKASI RAPID MINER - J. Anggun Rumboirusi; Nahema Yaroseray; Kartensia Firli Rumboirusi; Jessica Dumpel; Lamberth Anthoni Yores Rumbino; Mariani Regina Sisilia Lengkey; Heru Sutejo (Tamilis Synex: Multidimensional Collaboration, 2024)
This research aims to analyze cellphone sales predictions using the Naive Bayes algorithm which is implemented through the RapidMiner application. The dataset used consists of sales data with various relevant features, such as product descriptions, categories, and sales labels (sold or not sold). The research process involves several main stages, namely data retrieval (Retrieve), dividing data into train and test (Split Data), applying the Naive Bayes model, and evaluating performance using metrics such as accuracy, precision, and recall. The test results show that the Naive Bayes model succeeded in achieving accuracy, precision and recall levels of 100%. This indicates that the model has very good performance in classifying test data. However, to ensure the validity of the model, an analysis was carried out on the possibility of overfitting and suggestions for improvements such as using a larger dataset and testing using cross-validation. This research proves that the Naive Bayes method can be an effective and efficient solution for analyzing sales data patterns, especially in cases with structured and clear data patterns. The implementation of the results of this research can be applied as a basis for decision making in marketing strategy and inventory management.